The First Experience and Benefits of the 12-week VIVIFRAIL Exercise and Its Workout Music Selection for Elder Adults in the Community of Ardirejo, Kepanjen - Soenarti, Sri; Kurniawati, Victoria Maya; Zakiya, Fifi Afifatus; Pramesta, Marshanda Shella; Sulistyaningsih, Rita; Lestari, Harien; Amalia, Iftinan; Marintan, Silmy (Fakultas Kedokteran Universitas Brawijaya, 2024)
The VIVIFRAIL program is an Multi Component Physical Exercise (MPC) program which includes strength trainings, aerobics, gait trainings, balance and flexibility exercises tailored for each individual, and designed to facilitate evidence-based exercise interventions for elder adults. This program, which is unprecedented in Indonesia, is targeting elder adults in the pre-frail stage who are aiming for robust or fit status. This study utilizes a qualitative method with 15 older adults as the respondents. The data was collected from semi-structured interviews to encourage respondents to openly share their experience on the VIVIFRAIL program. The Consolidate criteria for Reporting Qualitative research (COREQ) method is used for reporting. The objective of this study is to find out the elderly's first experience of participating in VIVIFRAIL exercise and its benefits in returning the elderly's physical performance to robust or fit status as well as the selection of accompanying music during the 12 week exercise in the Ward Area of Ardirejo, Kepanjen District. The results showed that our respondents experienced positive feeling and felt physically fit and fresh. They could also monitor their blood pressure and train their balance to avoid falling. Moreover, after getting the benefit, respondents expected that the program could be continued. As for the workout music selection, respondents chose Javanese traditional music (gending), dangdut/koplo, local music, campursari, oldies songs, and Malangan songs for accompanying their exercise. In conclusion, after participating in the VIVIFRAIL program for 12 weeks, the respondents felt positive and physically fit and fresh.